An Investigation of the Oil and Gas Geopolitical Situation in the Eastern Mediterranean Region - Norouzi, Nima (Current Alternative Energy, 2022)
One of the main global energy struggles in recent years has been in the Eastern Mediterranean. In cooperation with Egypt and Israel, Greece and the Greek Cypriot government (GCA) are implementing a containment strategy against Turkey and the Turkish Republic of Northern Cyprus (TRNC). Turkey’s response to this plan was an exclusive agreement with Libya. Turkey and Libya have signed a memorandum of national reconciliation on limiting the new continental shelf’s maritime jurisdiction in the Eastern Mediterranean - the only borders of the shared economic zone. Greece could act with other countries, and it is said that Turkey’s competence will be ratified in the face of agreements that may restrict movement. The United States and the European Union (EU) also sought to share gas with European countries against Turkey, Israel, and the GCA. This article focuses on Libya’s ongoing competition, given Libya’s oil geopolitics and challenges in the eastern Mediterranean region. This paper briefly investigates the energy geopolitics in the eastern Mediterranean and North African regions; this paper aims to conclude the diverse opinions led by various interests and points of view and suggests a solution for the ever-growing tensions in this region.• Introduction• Literature Review• Geopolitics of Region• Discussion• Conclusion
Keywords: Petropolitical ambient